Computing turning point monthly probability of the Argentinian economy according to the leading index: 1973 - 2000 - Jorrat, Juan Mario; Cerro, Ana María (Estudios de Economía, 2016)
Two indicators of the Argentinean economic cycle prove to be useful for economic forecasts, the leading and coincident indexes. The former points out the level of economic activity monthly. The latter anticipates the future direction of the economy. The purpose of this paper is to estimate the monthly peak and trough probabilities, in the business and growth cycles using the Neftci’s sequential probability recursion. We first determine the probability density function that best adjusts to the observed frequency of the monthly leading index rate of change. The results obtained by the probabilities are evaluated in each case.